Competence-induced protein Ccs4 facilitates pneumococcal invasion into brain tissue and virulence in meningitis. Issue 1 (31st December 2018) - Hirose, Yujiro; Yamaguchi, Masaya; Goto, Kana; Sumitomo, Tomoko; Nakata, Masanobu; Kawabata, Shigetada
ABSTRACT: Streptococcus pneumoniae is a major pathogen that causes pneumonia, sepsis, and meningitis. The candidate combox site 4 ( ccs4 ) gene has been reported to be a pneumococcal competence-induced gene. Such genes are involved in development of S. pneumoniae competence and virulence, though the functions of ccs4 remain unknown. In the present study, the role of Ccs4 in the pathogenesis of pneumococcal meningitis was examined. We initially constructed a ccs4 deletion mutant and complement strains, then examined their association with and invasion into human brain microvascular endothelial cells. Wild-type and Ccs4-complemented strains exhibited significantly higher rates of association and invasion as compared to the ccs4 mutant strain. Deletion of ccs4 did not change bacterial growth activity or expression of NanA and CbpA, known brain endothelial pneumococcal adhesins. Next, mice were infected either intravenously or intranasally with pneumococcal strains. In the intranasal infection model, survival rates were comparable between wild-type strain-infected and ccs4 mutant strain-infected mice, while the ccs4 mutant strain exhibited a lower level of virulence in the intravenous infection model. In addition, at 24 hours after intravenous infection, the bacterial burden in blood was comparable between the wild-type and ccs4 mutant strain-infected mice, whereas the wild-type strain-infected mice showed a significantly higher bacterial burden in the brain. These results suggest that Ccs4 contributes to pneumococcal invasion of host brain tissues and functions as a virulence factor.